2021
DOI: 10.3390/ijerph18094401
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Clostridium botulinum in Food Using Loop-Mediated Isothermal Amplification (LAMP)

Abstract: Botulinum neurotoxins are considered as one of the most potent toxins and are produced by Clostridium botulinum. It is crucial to have a rapid and sensitive method to detect the bacterium Clostridium botulinum in food. In this study, a rapid detection assay of C. botulinum in food using loop-mediated isothermal amplification (LAMP) technology was developed. The optimal primers were identified among three sets of primers designed specifically based on the partial ntnh gene encoding nontoxic-nonhaemagglutinin (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…Isothermal amplification is an ideal technology to overcome the disadvantages of PCR-based methods. The loop-mediated isothermal amplification (LAMP) has been widely used in pathogen detection ( 13 , 14 ). However, a relatively high rate of false-positive results is a shortcoming of the LAMP method ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isothermal amplification is an ideal technology to overcome the disadvantages of PCR-based methods. The loop-mediated isothermal amplification (LAMP) has been widely used in pathogen detection ( 13 , 14 ). However, a relatively high rate of false-positive results is a shortcoming of the LAMP method ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Garg et al [ 40 ] introduced successful LAMP-based turbidimetric detection of Mycobacterium leprae targeting the 16s rRNA gene. Likewise, similar studies reported the detection of multiple pathogens—for instance, Clostridium botulinum [ 41 ], Streptococcus pneumoniae [ 42 ], and Streptococcus agalactiae [ 43 ]. However, this method provides low sensitivity, as the faint product can easily be misjudged.…”
Section: Lamp Detection Methodsmentioning
confidence: 99%
“…However, although many long primers increase the reaction yield, a risk of primer dimerization owing to nonspecific interactions simultaneously exists [9,27]. To prevent primer dimerization, adding dimethyl sulfoxide (DMSO) and betaine is used as a strategy to decrease nonspecific interactions, thereby giving stability to oligonucleotides [28]. The use of additional compounds can amplify nucleic acids without non-specific amplification, and exponential nucleic acid amplification is achieved while forming loops within 40-60 min at a constant temperature of 60-65 • C [29].…”
Section: Isothermal Amplification Methodsmentioning
confidence: 99%